Memahami Teori-Teori Perilaku Belajar Dalam Organisasi - Muniroh, Alimul (MADINAH, 2014)
Learning is a fundamental process of behavior change as a result of experience in an organization/institution (George & Jones, 2008). Learning is not only important for new members, but also long-time members at all levels of the organization because old members are often assigned tasks they have never worked before. Learning is a change in behavior and knowledge that is relatively long from the results of practice and experience.